2005
DOI: 10.1108/00907320510611366
|View full text |Cite
|
Sign up to set email alerts
|

Digitizing a gap: a state‐wide institutional repository project

Abstract: PurposeThis study aims to illustrate how one medium‐sized academic library was able to use a web‐based digitization and repository project to increase and promote communication and relationships between the library and the university community. This case study traces the history and development of the Cornerstone Project – the Network of Alabama Academic Library's (NAAL) state‐wide digital repository project.Design/methodology/approachThe paper describes the steps taken by a medium‐sized academic library to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The early case studies included the introduction of Trinity University Library's project, 4 Rochester Institute of Technology's experience, 5 and the Network of Alabama Academic Library's efforts. 6 All of the authors had various levels of involvement in the planning and setting-up of their institutional repositories, which provided them with ideas and information to describe the background of their project undertaking. Each experience details the entire process of repository development by their libraries and specifies every development step from the assessment of users' needs to the marketing of the repositories.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The early case studies included the introduction of Trinity University Library's project, 4 Rochester Institute of Technology's experience, 5 and the Network of Alabama Academic Library's efforts. 6 All of the authors had various levels of involvement in the planning and setting-up of their institutional repositories, which provided them with ideas and information to describe the background of their project undertaking. Each experience details the entire process of repository development by their libraries and specifies every development step from the assessment of users' needs to the marketing of the repositories.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Generally speaking, due to the use of ICT, the global system of scientific communication developed and new opportunities were presented for the faculty, staff and students to share their work with a number of people without the reliance on the traditional publishing venues (Graham et al , 2005). The widespread availability of electronic content created opportunities for new forms of research and scholarship that are qualitatively different from the traditional way of using academic publications and research data (Arms and Larsen, 2007).…”
Section: Influence Of Ict On Scientific Communicationmentioning
confidence: 99%
“…In Han's (2004, p. 356) analysis of a content management system, he revealed that the University of Arizona Library developed a number of digital projects and “a group was formed to include people with expertise in computer technology, metadata and systems analysis”. Similarly, the Network of Alabama Academic Libraries initiated a series of “training workshops on topics ranging from the physical mechanics of scanning to creating metadata” (Graham et al , 2005, p. 340) in the realization of their cornerstone project. Mittal and Mahesh (2008) connoted that regular training programmes are commonly practiced amongst digital libraries and IR centres in India.…”
Section: Literature Reviewmentioning
confidence: 99%